IMPROVING OCCUPATIONAL SAFETY IN BUILDING MATERIAL RETAIL THROUGH HIRA AND JSA - Kurnia, Ratih Dianingtyas; Septiyandi, Muhammad Aldo; Cahyo, Winda Nur (Journal of Industrial Engineering Management, 2025)
Construction and material shops involve various high-risk activities, making Occupational Safety and Health (OSH) practices essential. This study aims to build a clear picture of existing safety practices and key risks in building material retail requiring attention through structured safety initiatives. Based on the findings, this study provides recommendations to improve OSH practices for workers in these environments. HIRA (Hazard Identification and Risk Assessment) and JSA (Job Safety Analysis) methods were employed to identify potential occupational hazards by defining the characteristics of possible hazards and evaluating associated risks. The findings reveal several unsafe acts and conditions from various working process and activity leading to potential hazards. A total of eight potential hazards were identified with HIRA uncovering one extreme risk, three very high risks, three high risks, and one medium risk. Among these potential hazards, manual handling posing the highest risk, followed by ergonomic issues, dust exposure, and contact with sharp objects where all classified as very high risks. To mitigate these risks, by using JSA, a combination of engineering controls, administrative measures, and PPE use was recommended in order to improve material handling, workstation conditions, and safety equipment usage. These recommendations serve as the foundation for implementing a proper OSH management system.